Random vibration analysis of 3-Arc-Fan compliant interconnects - Chung, Philip Y.; Sitaraman, Suresh K. (Microelectronics and reliability, 2018)
Microelectronic packaging compliant interconnects offer increased reliability when compared to traditional rigid solder ball interconnects. These interconnects are subject to various forms of mechanical damage including thermal cycle fatigue, drop impact shock, and vibration environments that often lead to mechanical or electrical failure. Second-level compliant interconnects seek to alleviate this issue by decoupling the substrate and board, facilitating independent deformation while experiencing lower stresses and strains. In order to develop compliant interconnects as an effective alternative to rigid solder balls, various design optimization, thermal cycling test, and drop impact studies have been performed. However, the area of vibration characterization and analysis is lacking for microelectronic packaging and nonexistent for compliant interconnects. Therefore, this paper will present a complete vibration analysis of a particular multi-path compliant interconnect design, the 3-Arc-Fan compliant interconnect. This design features three electroplated copper arcuate beams that provide a spring-like effect to increase compliance and mechanical reliability. Experimental vibration characterization was performed and used to validate the simulation model. Following which a random vibration analysis method wais established, and the samples were tested at various conditions. Finally, both experimental and simulation results were integrated to develop a preliminary fatigue life prediction model to demonstrate the increased reliability. •A random vibration analysis of a novel 3-Arc-Fan compliant interconnect is performed.•Established analysis methodology for both experimental and simulation components•A preliminary fatigue life prediction model is developed for the structure.•The 3-Arc-Fan demonstrates increased reliability compared to solder BGAs.